Analisis Framing Komunikasi Politik Jokowi tentang Indonesia Emas 2045 di Media Online detik.com dan Kompas - Bintang Ramadhan; Arfian Suryasuciramdhan; Deden Deden (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Elections are a voting process carried out by voting by all Indonesian people every 5 years. Elections in 2024 will be held simultaneously to elect legislative candidates such as the DPR and executive candidates such as the President and Vice President. In the 2024 election period, during the ongoing process there was political involvement carried out by the 7th President of the Republic of Indonesia, namely Joko Widodo. Because the Candidate Pairs (Paslon) involved have a close relationship with Jokowi. In order to achieve Indonesia's target as a developed country and achieve Golden Indonesia 2045, targets must be achieved. Therefore, determining the next leader is very important in order to lead Indonesia to become a developed country.